2020
DOI: 10.2478/quageo-2020-0034
|View full text |Cite
|
Sign up to set email alerts
|

Unity in Variety. Employment Dynamics and Specialisation Profiles of Medium-Sized Towns in the Asti-Rovigo Area, Italy (2001–2017)

Abstract: We still know relatively little about the processes of economic transformation in medium-sized towns, which are the cornerstone of the settlement system of many rural areas, together with small towns. This paper considers a group of 39 towns in Northern Italy, located in the area between Asti and Rovigo. Using data from the Italian National Institute of Data Statistics (ISTAT), we investigated the dynamics of the number of the employed at businesses in the periods of 2001–2011 and 2012–2017, the different spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, the empirical evidence is ambiguous. A sample of 39 SMSTs in northern Italy showed that industrial towns face poorer job growth and are more prone to economic crises (Clerici, 2020). Ženka et al (2015) found a generally positive relationship between the share of manufacturing employment and economic performance in Czech non-metropolitan microregions with an average population of 42,000, noting that older industrial microregions with a dominant single industrial firm tend to have high per capita value added.…”
Section: Socioeconomic Performance and Transformationsmentioning
confidence: 99%
“…However, the empirical evidence is ambiguous. A sample of 39 SMSTs in northern Italy showed that industrial towns face poorer job growth and are more prone to economic crises (Clerici, 2020). Ženka et al (2015) found a generally positive relationship between the share of manufacturing employment and economic performance in Czech non-metropolitan microregions with an average population of 42,000, noting that older industrial microregions with a dominant single industrial firm tend to have high per capita value added.…”
Section: Socioeconomic Performance and Transformationsmentioning
confidence: 99%
“…MSCs have an entirely unique position in the settlement network, but it is difficult to form an overarching account of their characteristics and evolutionary processes: even within the same country (and even within the same region) we find many scenarios, defined by a mix of factors linked to geographical position, the socio-economic fabric and local political stances. These cities form a group in appearance only, finding unity in their variety (Clerici, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of medium-size cities for comprehensive support with the development policy is connected to the fact that they play a significant stabilizing role in the polycentric settlement system [5,6]. The proper formation and functioning of that system positively influences territorial cohesion, reduces development disproportions and tendencies for excessive concentration, lowers activity costs, increases the probability of synergy effects, weakens negative feedback, and enables complementary network cooperation [7,8].…”
Section: Introductionmentioning
confidence: 99%